Isolasi, Karakterisasi, dan Uji Bioaktivitas Metabolit Sekunder dari Hydroid Aglaophenia cupressina Lamoureoux Sebagai Bahan Dasar Antimikroba - Eva Johannes; Hanapi Usman; Ahyar Ahmad (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2009)
Isolation, structure elucidation, activity test against Salmonella thypi, Staphylococcus aureus of secondary metabolite from hydroid Aglaophenia cupressina Lamoureoux, were conducted. This study was aimed to identify and isolate the compound with antibacterial properties of hydroid Aglaophenia crupessina Lamoureoux. This study used stepwise method with the following sequences: extraction, isolation, purification, structure elucidation, and bioactivity test. Study results indicated three compounds found: (1)carboxylate acid compound: hexadecanoic acid and has antibacterial properties; (2) alkaloidcompound which was considered as a new compound: aglaounhas and has antimicrobialproperties; (3) steroid compound: β-sitosterol with no antimicrobial properties.Keywords: Isolation, characterization, secondary metabolite, Aglaophenia cupressina, Antibacterial.